Combinatorial Implications of Nrf2 Inhibitors with FN3K Inhibitor: In vitro Breast Cancer Study - Beeraka, Narasimha M.; Zhang, Jin; Zhao, Di; Liu, Junqi; A.U., Chinnappa; Vikram P.R., Hemanth; Shivaprakash, Priyanka; Bannimath, Namitha; Manogaran, Prasath; Sinelnikov, Mikhail Y.; Bannimath, Gurupadayya; Fan, Ruitai (Current Pharmaceutical Design, 2023)
Background: Platinum derivatives are chemotherapeutic agents preferred for the treatment of cancers including breast cancer. Oxaliplatin is an anticancer drug that is in phase II studies to treat metastatic breast cancer. However, its usage is constrained by chemoresistance and dose-related side effects.Objective: The objective of this study is to examine the combinatorial efficacy of brusatol, an Nrf2 blocker, with oxaliplatin (a proven FN3K blocker in our study) in mitigating breast cancer growth in vitro.Methods: We performed cytotoxicity assays, combination index (CI) analysis, colony formation assays, apoptosis assays, and Western blotting.Results: Results of our study described the chemosensitizing efficacy of brusatol in combination with lowdose oxaliplatin against breast cancer through synergistic effects in both BT-474 and T47D cells. A significant mitigation in the migration rate of these cancer cells was observed with the combination regimen, which is equivalent to the IC-50 dose of oxaliplatin (125 μM). Furthermore, ROS-mediated and apoptotic modes of cell death were observed with a combinatorial regimen. Colony formation of breast cancer cell lines was mitigated with a combinatorial regimen of bursatol and oxaliplatin than the individual treatment regimen. FN3K expression downregulated with oxaliplatin in T47D cells. The mitigation of FN3K protein expression with a combination regimen was not observed but the Nrf2 downstream antioxidant signaling proteins were significantly downregulated with a combination regimen similar to individual drug regimens.Conclusion: Our study concluded the combination efficacy of phytochemicals like brusatol in combination with low-dose oxaliplatin (FN3K blocker), which could enhance the chemosensitizing effect in breast cancer and minimize the overall dose requirement of oxaliplatin.
Keywords: Nrf2 blocker